Using scenarios to derive software - Hadad, Graciela Dora Susana (2009)
The present thesis describes a Requirements Engineering strategy, called SDRES (Scenario Driven Requirements Engineering Strategy), which proposes to face topics rarely treated in real practice, such as continuous changes in requirements, software defects originated during requirements production, the organisational context surrounding the software system and the treatment of quality requirements.